UiT The Arctic University of Norway Culture and Social Sciences Library - Interior ... : UiT Norges arktiske universitet Universitetsbiblioteket – Kultur- og samfunnsfag ... - Campbell, Sandy (University of Alberta Library, 2024)
One of the main libraries on the UiT campus in Tromsø, the Culture and Social Sciences Library has open book stacks on several floors, as well as study carrels and casual seating. In this image a chess set sits on a table between two orange couches. ...